AL-TA'BIR AL-ISTHILAHI WA ISTI'MALATUHU FI KITAB SILSILAH TA'LIM AL-LUGHAH AL-'ARABIYAH - Rahman, Faridah; Abd. Safa, Najmuddin (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
This article aims to discuss Arabic idioms and their use in Book